What you need to know about leadership - Grout, Jeff (Capstone, 2011)
Leaders make or break organisations? The difference between companies which soar and those which fail is often just the difference between good and bad leaders. And it's not just the CEO who needs to be a leader? Every manager needs to lead. But what is leadership, anyway, and how can you do it?